Investigating factors that influence change from a traditional to asocio-constructive teaching paradigm: Teachers’ beliefs, alternate conceptions and external factors - Von Oppell, Monika Ann (Curtin University, 2016)
This study sought to better understand teachers’ implementation of reform initiatives. Multiple research methods, including surveys (N=198 teachers), interviews and observations (N=15 case study teachers) highlighted an incongruence between teachers’ perceived and observed practice. Important factors that influenced implementation were identified, including: lack of knowledge of constructivist practice; misinterpretation of terminology; time constraints; and lack of support from the school administration. The findings could assist in better understanding change in teachers’ practice during education reform.